Echoism: Is there a place for Echoism in Existential Analysis? (Existential Analysis: Journal of the Society for Existential Analysis, 2015)
This paper is the beginning of a study of a largely neglected subject. In the prevailing psychoanalytic and psychological literature on Narcissism, Echo is treated as an object in relation to Narcissus, and as such has her own voice is absent. Through reclaiming Echoism as a subject in its own right, and engaging with Sartre's classifications of Being, The Look and Impersonation, this paper considers how we might arrive at an important theoretical distinction between two applications of the term and remain available to the specific needs of the Echoistic client in clinical work.
Keywords: Echo; Echoism; Echoistic; Narcissism; Labels; Myth; Sartre; Being; Nothingness; Being-in-itself; Being-for-itself; Being-for-others; Being-through-others; The Look; Impersonation; Psychoanalysis; Projection; Active Introjection; Responsibility; Defensive Echoist; Self-destructive Echoist; Voice